The Demise of Sufi Values in Islamic Educational Institution: Bullying in Madurese Pesantrens - Muhlis, Achmad; Cholid Wardi, Moch.; Baiquni, Ach; Septiadi, Dimas Danar; Mansurnoor, Iik Arifin (Ulumuna, 2025)
The recent exposure of bullying in pesantren has raised an irony, threatening its reputation as a safe place to prepare students (santri) with motivation, self-reliance, well-character, and dedication. This research explores bullying in pesantrens in Madura, East Java, Indonesia. It employs a qualitative and critical descriptive approach and hypothetically relates the bullying to the demise of sufi values in the pesantren. Purposely selecting six pesantren (two from each type: Salaf, semi-modern, and modern) as samples, with respondents consisting of students, teachers and staff, this research seeks to accommodate the complexity of patterns or types that might have contributed to how bullying takes place and how it may relate to some sufi values. It turns out that among several types, bullying occurs most prevalently between students and teachers (ustadh), serving interchangeably as doers and victims. This can be as much related to social hierarchy within the pesantren as to the double roles that both play. The bullying indicates the demise of sufi values and can be attributed to at least four factors: insufficient contextualization during the learning process, imbalanced reading materials for the subject, an ineffective learning process, and a hierarchical atmosphere among the participants.